SIPAMBULAN: Sistem Informasi Pelayanan Ambulan menggunakan Algoritma Djikstra - Susanto, Agus; Purwaningrum, Santi (Infotekmesin, 2023)
The rapid development of information technology encourages innovation in various fields, including the field of disaster geographic information services. Lack of information on ambulance service providers is often the cause of delays in handling victims of natural disasters. Besides, the absence of information regarding the nearest route for ambulances to emergency service providers such as health centers and hospitals adds to the length of time for handling victims of natural disasters, resulting in increasingly severe victim losses, including life. This study aims to create a geographic information system that can be used to provide information on the location of the nearest ambulance service provider and emergency unit service. The system development research method uses the extreme programming method by implementing the Djikstra algorithm to determine the shortest route. This system testing process consists of testing the Djikstra algorithm and testing functionality using a usability scale. Djikstra's algorithm testing is done by comparing the results of calculating the shortest route for two location points with the results obtained when using the Google Maps application. The results of this test indicate that the system can display shorter routes than the routes generated by the Google Maps application. On the other hand, testing system functionality using the usability scale method to see system acceptance by users shows that the application can be used properly with a score obtained that is 77.